Analisis Quantitative Planning Matrix (QSPM) pada Potensi Wisata Air Terjun Agal Desa Marente - Wahyu Ardiansyah; Rozzy Aprirachman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Nature-based tourism development has a strategic role in encouraging sustainable local economic growth, especially in rural areas such as Marente Village, Kabupaten Sumbawa. Agal Waterfall is one of the natural tourism destinations that has high attractiveness, but its utilization is still not optimal due to limited facilities and infrastructure, access to the location, promotional activities, and the quality of human resources management. This study aims to identify strengths, weaknesses, opportunities, and threats, and determine priority strategies in developing Agal Waterfall tourism using the Quantitative Strategic Planning Matrix (QSPM) method. The research approach used is descriptive quantitative with primary data collected from 100 respondents. Analysis techniques include the preparation of IFAS, EFAS, SWOT, and QSPM matrices. The research findings show that the beauty of the natural environment and community participation are the main strengths, while the limited supporting facilities and promotion are still the dominant weaknesses. Development opportunities are supported by the increasing interest in nature tourism and the utilization of digital platforms, while threats come from competition between tourist destinations and the potential for environmental degradation. Based on the results of the analysis, priority strategies suggested include improving basic facilities, optimizing digital-based promotions, strengthening the capacity of human resource managers, and implementing the principles of sustainable tourism.